The Effect of Providing Animated Videos of Dengue Fever on Knowledge and Attitudes of Students of Singajaya 2 Elementary School - Amirah; Eko Maulana Syaputra; Sukhriyatun Fitriyah (Cleanliness: Journal of Health Sciences and Medical Research, 2025)
Background : The number of dengue fever (DBD) cases in Indramayu Regency in 2023 was 171 cases with 9 deaths. In the area of Plumbon Community Health Center,including Singajaya, there were 20 cases of dengue fever from January to May 2024. These cases mostly affected children aged 7-12 years. Objective : This research aims to investigate the influence of dengue fever animated video media on students of SD Negeri 2 Singajaya. Research Method : This study used a quantitative research method, namely quasi-experimental with a one-group pre-test post-test design. The sampling technique used Total Sample with 43 samples of students in grades 5 and 6. Data collection method used Pre-test and Post-test sheets. Data analysis used univariate and bivariate analysis with the Wilcoxon test. Research Results Based on the research results, before the animated video was given, the knowledge level was in the Fair category 34.9%, and Poor 65.1%. The respondents' attitudes before the animated video were categorized as Fair 58.1% and Poor 41.9%. After the animated video was given, there was a change in the knowledge level with Good category 20.9%, Fair 39.5%, and Poor 39.5%. The respondents' attitudes after the treatment were categorized as Good 25.6%, Adequate 48.8%, and Inadequate 25.6%. Conclusion  : Based on the Wilcoxon test results, a p-value of <0.003 was obtained, which means there was an increase in knowledge and attitudes of the students after the animated video was given. There is an influence before and after the provision of dengue fever animated video on the knowledge and attitudes of the students. Based on the research results, it is hoped that animation media can be used as an outreach medium, and future researchers are expected to be able to research the practice of implementing dengue fever prevention